Hubungan Perilaku Ibu Terhadap Hidup Bersih Dan Sehat (PHBS) Dengan Kejadian Diare Pada Balita Di Wilayah Kerja Puskesmas Boloh Kecamatan Toroh Kabupaten Grobogan - Setiyani, Desi, dr. Burhanudin Ichsan M.med.Ed, dr. Yusuf Alam R, M.K (2016)
Background: The incidence of diarrhea worldwide is still quite high. Villagers Boloh not all apply PHBS and annually increased diarrheal disease that attacks all age groups. This study aims to know the relation of PHBS with the incidence of diarrhea in infants. Methods: This study is observational analytic research using cross sectional design that is carried on 21 December 2015 in the Boloh Community Health Center Sub-district Toroh District Grobogan. The study population was all the mothers who have children aged 2 months - 5 years amounted to 50 people. While sampling used Probability Sample with Cluster Random Sampling technique. Results: This study analyzed using Chi-square test and get the results (x2) = 3,004 with p-value = 0.083. Conclusions: There was no relation between mothers behavior about Clean and Healthy Lifestyle (PHBS) With the Incidence of Diarrhea In Infant and Toddler In The Boloh Community Health Center Sub-district Toroh District Grobogan. Essay. Faculty of Medicine, University of Muhammadiyah Surakarta.